I’ll Meet You in Metaxis: The Potential of Drama in Fostering Parental Emotional Literacy with Preadolescent Children in Mainland China - Qi, Jia Jia (Trinity College (Dublin, Ireland). School of Education, 2021)
This study investigates the potential of drama as an intervention to foster parental emotional literacy with preadolescent children. The literature review examines the importance of preadolescent emotional literacy and parental emotional literacy. The factors and barriers that have an impact on preadolescent emotional growth and the role of parents are explored in both in general and within the Chinese context. This is a desktop study using secondary information from printed books and online resources. A conceptual framework named ‘The Metaxis Process’ is created. The findings from the literature review related to the importance of preadolescent emotional literacy and parental emotional literacy revealed a lack of parental awareness towards the emotional development of preadolescent children in families in Mainland China. Therefore, a conceptual drama programme was designed for future use with a small group of Chinese parents of preadolescent children. The findings imply that DiE (Drama in Education) and Augusto Boal’s drama could meet in the metaxis and have the potential to foster parental literacy through a process of safety, communication, reflection and understanding. To achieve a more holistic understanding of the relationship of the emotional world between Chinese parents and their preadolescent children and of the potential of drama in fostering this relationship, the study recommends that empirical work should be implemented with both parents and children.
Keywords: Drama in Education; Education